TECHNOLOGY ACCEPTANCE MODEL AS A PREDICTOR OF SIMDA USAGE - Devi Febrianti; Bambang Hariadi; Zaki Baridwan (Jurnal Reviu Akuntansi dan Keuangan, 2019)
The study aims to analyze behavioral aspects, especially individual factors that influence the use of SIMDA using the Technology Acceptance Model theory (TAM). The population in this study were all financial managers in all Organisasi Perangkat Daerah (OPD) in the Pemerintah Kabupaten Pasuruan with a total sample of 282 respondents. The samples selected by judgment sampling method. Analysis technique using PLS (Partial Least Square) with WarpPLS 5.0 software The findings of this study, first, job relevance and result demonstrability is positively related to perceived usefulness. Second, perceived ease of use, perceived enjoyment, and  perceived usefulness is positively related to attitude. Third, perceived usefulness and attitude is positively related to behavioral intention. Furthermore, behavioral intention is positively related to behavior of SIMDA usage.